Psychometric Evaluation of the Summary of Diabetes Self-Care Activities–Arabic (SDSCA-Arabic): Translation and Analysis Process - AlJohani, K.; Kendall, Garth; Snider, P. (2016)
Purpose: To translate and examine the psychometric properties of the Arabic version of the Summary of Diabetes Self-Care Activities. Design: An instrument translation and validation study. Settings: A total of 243 participants (33 first sample and 210 second sample) diagnosed with type 2 diabetes mellitus were recruited from four primary health care centers in Saudi Arabia. Methods: The study was guided by the World Health Organization guidelines for translation and validation of instrument. Results: Translation indicators showed satisfactory outcomes for each included process in the forward-translation, an expert panel, and back-translation stages. Reliability and validity outcomes were as follows: test–retest, r = .912 and p < .001; split-half = .9; and Cronbach’s alpha (α) = .76. The alpha scores for the subscales were as follows: diet, .89; exercise, .83; blood glucose testing, .92; and foot care, .77. Principal component analysis revealed the presence of four components with eigenvalues greater than 1.0, explaining 34.4, 16.4, 15.4, and 11.2% of the variance in everyday practices for these items, respectively (accumulated = 77.1%). Conclusions: The translation and validation processes revealed acceptable psychometric properties. The instrument could evaluate diabetes self-care in Saudi Arabia and has the potential to be used in other Arabic-speaking populations.